Reliability Life Estimation Considered fault Correlation of Aerial Bearing. Issue 4 (January 2021) - Song, C; Bian, Z; Ding, S N
Abstract: The purpose of this paper is to study the reliability life calculation model of aerial rolling bearing considered the correlation of failure model. By mean of collecting relevant experiment data of vibration signal and temperature signal in the life test of the aerial rolling bearings, and analyse time domain and frequency domain, we can analyse the main failure modes and mechanism (e.g. wear, fatigue). The characteristic parameters that characterize the healthy state of aerial rolling bearings obviously are extracted further. Considering that the bearings expose multiple failure modes in the working process in most case, bearing fault diagnosis method is based on fuzzy theory. It is used to clarify the failure mechanism of different failure modes and the degradation rule of performance characteristic parameters. It's very essential that establish the clear relationships between performance degradation and symptomatic set. According to the fault diagnosis results, each of failure modes is established the performance degradation model respectively. Considering the correlation between multiple different failure modes, Copula theory is introduced to analyse the correlation between multiple failure modes. Base on Copula theory, it's obtained the life distribution model of aerial bearing based on multiple failure modes. Life distribution model are verified by subsequent experiments, which show that life distribution model of aerial rolling bearing in this paper, is feasible and necessary.